2020
DOI: 10.1111/bjd.18857
|View full text |Cite
|
Sign up to set email alerts
|

A multicentre, randomized, double‐masked, parallel group, vehicle‐controlled phase IIb study to evaluate the safety and efficacy of 1% and 3% topical minocycline gel in patients with papulopustular rosacea

Abstract: Summary Background Papulopustular rosacea is characterized by chronic facial erythema and inflammatory facial lesions. Minocycline has anti‐inflammatory properties which may be effective in the treatment of rosacea inflammatory lesions. Objectives To assess the safety and efficacy of once‐daily topical minocycline gel 1% and 3% in patients with papulopustular rosacea. Methods This was a prospective, 12‐week, double‐blinded study conducted at 26 sites in the United States; 270 patients with papulopustular rosac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
23
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 13 publications
0
23
0
Order By: Relevance
“…The efficacy and safety of minocycline foam for the treatment of moderate to severe papulopustular rosacea were evaluated and confirmed in two phase 3, randomized clinical trials (751 and 771 participants, respectively) [ 18 ]. A prospective, 12-week, double-blinded study including 270 patients showed that 3% topical minocycline gel benefitted patients with papulopustular rosacea, significantly decreasing inflammatory lesions compared to vehicle [ 31 ]. A higher proportion of patients using minocycline gel achieved success according to an Investigator's Global Assessment.…”
Section: Topical Therapiesmentioning
confidence: 99%
“…The efficacy and safety of minocycline foam for the treatment of moderate to severe papulopustular rosacea were evaluated and confirmed in two phase 3, randomized clinical trials (751 and 771 participants, respectively) [ 18 ]. A prospective, 12-week, double-blinded study including 270 patients showed that 3% topical minocycline gel benefitted patients with papulopustular rosacea, significantly decreasing inflammatory lesions compared to vehicle [ 31 ]. A higher proportion of patients using minocycline gel achieved success according to an Investigator's Global Assessment.…”
Section: Topical Therapiesmentioning
confidence: 99%
“…In the USA, where state-level registry reporting of incident cases is not mandatory, NMSC results in annual healthcare costs of~$426 million among Medicare patients, making it the fifth costliest after prostate, lung, colon and breast carcinomas. 2 Prevention remains a key factor in reducing incidence, with avoidance or reduction of solar radiation exposure being paramount. Nevertheless, identification of ubiquitous risk factors and/or effect modifiers of ultraviolet exposure is crucial for reducing this burden.…”
Section: Conflicts Of Interestmentioning
confidence: 99%
“…In this issue of the BJD, Webster et al report the beneficial effects of topical minocycline on papulopustular rosacea. 2 The precise mechanism of action of tetracyclines in rosacea remains unclear. Multiple anti-inflammatory effects have been reported including inhibition of proinflammatory cytokines and matrix metalloproteinases, scavenging of reactive oxygen species, inhibition of neutrophil migration and adherence and reduced proliferation of lymphocytes.…”
mentioning
confidence: 99%
See 2 more Smart Citations